Preliminary Analysis of Linalool Extracted from Aspergillus-Fermented Pineapple Wastes towards Staphylococcus aureus - Lee, Chee Yan (2016)
Linalool is a monoterpene used widely in fragrance and household products industries. Linalool also has anti-microbial activity against Staphylococcus aureus. This study aimed to determine the optimal fermentation duration for both blended core and crown of Josapine using Aspergillus brasiliensis, to quantify the linalool content in the Aspergillus-fermented blended core and crown of Josapine, and to screen the anti-microbial potential of linalool extracted from both fermented blended core and crown of Josapine towards S. aureus. Production of linalool in this study was obtained through the fermentation of Josapine core and crown for three fermentation periods namely, Day-4, Day-8 and Day-12. After fermentation, the fermentation broths of the blended core and crown were extracted for linalool using dichloromethane. The crude extracts of the fermented core and crown were separated using thin layer chromatography (TLC) and mobile phase methanol-ethylacetate. The presence of linalool in the isolated extracts were detected and visualized with phosphomolybdic acid (PMA) dye. Then, the absorbance of TLC-isolated linalool was measured at 300 nm using UV-spectrophotometer. The S. aureus culture was used to screen anti-microbial activity of TLC-isolated linalool. Fermentation using the blended core and crown showed significant differences in yielding linalool on Day-4 and Day-8 based on independent samples t-test. The concentration of linalool extracted from non-fermented blended crown and core were 21.548 mg/mL and 14.964 mg/mL respectively. Linalool concentration extracted from Day-4 fermented core and crown were 24.560 mg/mL and 15.773 mg/mL respectively. On Day-8, 1.481 mg/mL and 11.663 mg/mL linalool were extracted from respective fermented core and crown. The anti-microbial activity screening using TLC-isolated linalool from both fermented blended crown and core showed no inhibition of the growth for S. aureus. As a conclusion, Day-12 of fermentation was not chosen for linalool extracted as the percentage of viability lower was than Day-0. The linalool concentration extracted from the fermented blended core on Day-4 was found highest compared to non-fermented blended core while continuous decrement found in crown. Hence, crown was found not desirable to produce linalool through fermentation compared to core. Anti-microbial activity of linalool was proven using linalool standard (6 mg/mL) but not TLC-isolated linalool as the reactivity of linalool reduced due to the bound PMA.